The Relationship Between Restorative Justice Approach and the Authority of State Officials - Manubulu, Isakh B.; Neonbeni, Randy Vallentino; Mantolas, Kundrat; Buol, Glen Daniel Febrian Ongkio (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 2 (2024)DO - 10.24843/JMHU.2024.v13.i02.p01, 2024)
The adoption of the restorative justice approach for case resolution brings  signifies a transformative in Indonesia's criminal justice system. The discretion of state officials plays a pivotal role in determining the feasibility of restorative justice approach. This paper formulated in two issues: the relationship between restorative justice approach and the authority of state officials, as well as the boundaries of their jurisdiction in determining restorative justice approach. Formulated with  normative legal research methods and support by conceptual, analytical, and legislative approach. It concludes that the relationship between restorative jutice approach and the authority of state officials hinges on their discretionary interpretation of the suitability of utilizing the restorative justice approach for case resolution. Furthermore, the constraints on their discretionary authority are predominantly laid out in Law Number 30/2014 and in institutional regulations such as PERKAP 8/21 for police officials, PERJARI 15/20 for officials in the prosecutor's office, and judicial decisions like PERMA 1/2016 Jo. KMA Decision No. 108/KMA/SK/VI/2016.